PERILAKU KONSUMEN TERHADAP KESADARAN MENGGUNAKAN PRODUK KOSMETIK HALAL - INGGRITIA SAFITRI MASRUL; SEVIE SEVIE (Jurnal Bisnis dan Akuntansi, 2020)
Halal cosmetics is one of the halal products that are in demand by Muslim and non-Muslim communities in Indonesia. Public interest in halal cosmetics is influenced by several factors. The purpose of this study is to examine the factors of religious beliefs, self-identity, media exposure, perceived behavioral control, subjective norms, and attitudes towards behavior through the intention to consume halal cosmetics. The hypothesis of this study states that the factors of religious beliefs, self-identity, media exposure, behavioral control, subjective norms, and attitudes have an influence on behavior through the intention to consume halal cosmetics. This study used survey data from the distribution of questionnaires totaling 243 respondents, using SEM analysis and AMOS software. The results showed that a significant influence on consumer behavior to use halal cosmetics was the intention. Suggestion from this research is if the research uses the maximum likelihood approach, it will not be recommended to use more than 200 respondents, because it causes goodness of fit to be bad, but this research can also be presented with more respondents using other methods and analysis.